(untitled) (gjstudies, 2022)
This research investigates the multifaceted role of internal audit functions in advancing corporate governance objectives, with a particular focus on the integration of behavioral and technologicaldimensions often overlooked in traditional frameworks. While existing literature predominantly examines internal audit through compliance and risk management lenses, this study introduces a novelconceptual model that positions internal audit as a dynamic, interactive agent within the governanceecosystem. We propose that effectiveness is not merely a function of structural independence or procedural rigor, but is critically mediated by the audit function’s capacity for cognitive alignment withthe board and senior management, its strategic influence on organizational culture, and its adaptiveuse of technology for governance intelligence. Through a qualitative multi-case study methodologyinvolving in-depth interviews and documentary analysis across twelve diverse organizations, weuncover that the most effective internal audit functions employ a repertoire of ’soft’ influencing tactics, foster a culture of transparent dialogue beyond formal reporting lines, and act as early sensorsfor emerging governance risks. Our findings challenge the prevailing ’assurance-centric’ paradigmby demonstrating that internal audit’s greatest contribution to governance may lie in its ability tofacilitate learning, shape ethical decision-making norms, and bridge cognitive gaps between oversight bodies and operational management. The study concludes by offering a revised framework forassessing internal audit effectiveness, one that balances traditional metrics with behavioral and relational indicators, thereby providing a more holistic tool for boards and regulators seeking to optimizethis critical governance mechanism